On the need to better specify the concept of “control” in brain-computer-interfaces/neurofeedback research - Wood, Guilherme; Kober, Silvia Erika; Witte, Matthias; Neuper, Christa (Frontiers in Systems Neuroscience, 2014)
Aiming at a better specification of the concept of “control” in brain-computer-interfaces (BCI) and neurofeedback research, we propose to distinguish “self-control of brain activity” from the broader concept of “BCI control”, since the first describes a neurocognitive phenomenon and is only one of the many components of “BCI control”. Based on this distinction, we developed a framework based on dual-processes theory that describes the cognitive determinants of self-control of brain activity as the interplay of automatic vs. controlled information processing. Further, we distinguish between cognitive processes that are necessary and sufficient to achieve a given level of self-control of brain activity and those which are not. We discuss that those cognitive processes which are not necessary for the learning process can hamper self-control because they cannot be completely turned-off at any time. This framework aims at a comprehensive description of the cognitive determinants of the acquisition of self-control of brain activity underlying those classes of BCI which require the user to achieve regulation of brain activity as well as neurofeedback learning.